Perancangan Sistem Keamanan Parkir Sepeda Berbasis Radio Frequency Identification - Nurawan Rodiansyah; Hadian Satria Utama; Endah Setyaningsih (Universitas Tarumanagara, 2019)
These day, bicycle parking is available in many places, but many people still feel the lack of security in the parking area of the bicycle. The lack of security in the bicycle parking area available today can lead to the lack of bicycle users especially in Jakarta. To re-awaken bicycle users, some bicycle parking lots are made as safe as possible so that people are interested to park their bikes in a bicycle parking area. Bicycle parking spaces are designed to lock and unlock automatically and include a messaging system using GSM module to bicycle users containing SMS messages, As well as an alarm system that emits sound. Furthermore, when users want to take the bike, users need to attach RFID card to RFID Reader. Based on the test done, the LCD display